Biocontrol of bacterial wilt disease in tomato using Bacillus subtilis strain R31 - Sun, Yunhao; Su, Yutong; Meng, Zhen; Zhang, Jie; Zheng, Li; Miao, Shuang; Qin, Di; Ruan, Yulan; Wu, Yanhui; Xiong, Lina; Yan, Xun; Dong, Zhangyong; et al. (Frontiers in Microbiology, 2023)
Bacterial wilt disease caused by Ralstonia solanacearum is a widespread, severe plant disease. Tomato (Solanum lycopersicum), one of the most important vegetable crops worldwide, is particularly susceptible to this disease.Biological control offers numerous advantages, making it a highly favorable approach for managing bacterial wilt. In this study, the results demonstrate that treatment with the biological control strain Bacillus subtilis R31 significantly reduced the incidence of tomato bacterial wilt. In addition, R31 directly inhibits the growth of R. solanacearum, and lipopeptides play an important role in this effect. The results also show that R31 can stably colonize the rhizosphere soil and root tissues of tomato plants for a long time, reduce the R. solanacearum population in the rhizosphere soil, and alter the microbial community that interacts with R. solanacearum. This study provides an important theoretical basis for elucidating the mechanism of B. subtilis as a biological control agent against bacterial wilt and lays the foundation for the optimization and promotion of other agents such as R31.